TOPIC PREFERENCE OF SENIOR SECONDARY SCHOOL MATHEMATICS STUDENTS: THE ROLE OF GENDER - Adeleke, Joshua Oluwa (Sokoto Educational Review, 2020)
This study investigated the topic preference of Senior Secondary School Students in mathematics and the role gender plays on their preferences. Six hundred and forty Senior Secondary School II students selected through multi stage sampling were used. They provided data on their preferred topics in mathematics by giving positions to the nine major mathematics topics in the Senior Secondary School Syllabus. They equally indicated their gender. The data collected was analyzed using descriptive statistics (frequency, cross tabulation) Chi - square test was also used to test the impact of gender on student topic preference at the 0.05 level of significance. Number and Numeration, Algebraic process and Statistics were found to be most preferred Mathematics topics while Bearing, Probability and Mensuration are most disliked mathematics topic among Senior Secondary Students. Male and female students are found to be different in their preference for mathematics topics. It was also found that many male preferred Number and Numeration, Algebraic process, Mensuration and construction than their female counterpart is whereas many female students preferred Plane geometry, Trigonometry, Bearing, Statistics and Probability than male students. Based on the finding of this study, it was recommended that mathematics teachers should organize various result oriented classroom activities, initiate strategies and innovations especially on the topics identified as disliked mathematics topics that will boost interest of their students. School counselors also should make use of these findings especially the gender impact on the students’ preferences for mathematics topics to assist students overcome the dislike they have for some mathematics topics.